Surface- and deep-level diversity in panel selection — Exploring diversity effects on response behaviour in foresight - Spickermann, Alexander; von der Gracht, Heiko; Zimmermann, Martin (Technological Forecasting and Social Change, 2014)
In addition to foresight research endeavours that focus on the application of the Delphi survey technique, numerous research articles have dealt with the method itself: namely improving the Delphi technique's task and process characteristics. Particularly in Policy Delphi surveys and related variations that strive to explore opposing views, the diversity of the Delphi panel has been scrutinised. In the majority of earlier Policy Delphi studies, expertise accounted for the most predominant panel selection criterion. However, further surface- and deep-level diversity dimensions discussed in related social science research need to be incorporated for steering diversity in panel selection. In this article, the main effects of surface- and deep-level panel diversity on response behaviour are examined, focussing on extreme response style (ERS). Moreover, interaction phenomena of diversity variables are considered. By conducting a Policy Delphi in real-time format on the future of multimodal mobility, we demonstrate that value attributes significantly influence extreme response behaviour while expertise is especially important in combination with various other diversity variables. Furthermore, we identified a moderating effect of age on the relationship between environmental value characteristics and Delphi panellists' response behaviour.
Keywords: Panel diversity; Policy Delphi; Extreme response style (ERS); Sampling; Multimodal mobility